Italian Horse Riding School - Zbigniew Wójcik (Lesya Ukrainka Volyn National University, 2020)
The system solutions in the field of horse riding technique appeared for the first time in Italy in the 16th century, but at the same time equestrian academies also functioned in other countries, e.g. Austria, France, Germany and Russia. They formed the horse riding system which was based on such movements that horse never performs in its natural habitat. Therefore, according to the methodology research, applicable in historical and pedagogical sciences, an attempt was made to determine stages of the Art of Horsemanship on the European continent. In the research process, it was established that the horse riding style that had been being practiced for several centuries, was not changed until the late 19th century. The revolutionary changes, based on years of observation and experience, were made by Captain Federico Caprilli of the Military Equestrian School in Pinerolo (Italy). The result of his observations accepeted in 1906 was an innovative horse riding system called natural. A great numer of officers from 22 countries were coming to Italy at that time to learn the new system. As it was very practical, it became quickly adapted by equestrian sport.